Volatile compounds of some popular Mediterranean seafood species - GIOGIOS, I.; KALOGEROPOULOS, N.; GRIGORAKIS, K. (Mediterranean Marine Science, 2013)
The volatile compounds of highly commercialised fresh Mediterranean seafood species, including seven fish (sand-smelt Atherina boyeri, picarel Spicara smaris, hake Merluccius merluccius, pilchard Sardina pilchardus, bogue Boobps boops, anchovy Engraulis encrasicolus and striped-mullet Mullus barbatus), squid (Loligo vulgaris), shrimp (Parapenaeus longirostris) and mussel (Mytilus galloprovincialis), were evaluated by simultaneous steam distillation-extraction and subsequent GC-MS analysis. A total of 298 volatile compounds were detected. The mussels contained the highest total concentration of volatile compounds, while pilchard among fish species contained the highest number and concentrations of volatile compounds. Individual patterns of volatile compounds have been distinguished. The fish species when compared to the shellfish species studied, contained 6 to 30 times more 1-penten-3-ol, higher quantities of 2-ethylfuran, and 2,3-pentanedione, which was absent from the shellfish species. Pilchard is characterized by a high concentration of alcohols, shrimps by the high presence of amines and S-compounds, while mussels by high amounts of aldehydes, furans, and N-containing compounds (pyridine, pyrazines and pyrrols). The fatty acid-originating carbonyl compounds in fish seem to be related to the species’ fat content.